TANGGUNG JAWAB PIDANA DAN PERDATA BAGI NAKHODA TERHADAP TENGGELAMNYA KAPAL - R Juli Moertiono (LP2MTBM MAKARIOZ, 2019)
Sailing consists of transport in waters, ports, safety, and security of shipping and protection of the maritime environment is part of the national transportation system that should be developed its potential and role to realize an efficient and effective transportation system and to help create a steady and dynamic pattern of national distribution. Ships accident accident can be; sinking vessels, sailing vessels, shipwreck and burning boats caused by technical factors, natural factors/weather, and human factors. In the event of an accidental sinking of the ship, the skipper may be held accountable in both criminal and civil cases.